Leptodermis hechiensis (Rubiaceae), a new species from Guangxi, China - Guo, Xiao-Ming; Liao, Qi; Zhou, Shan; Wang, Rui-Jiang (Phytotaxa, 2018)
Leptodermis hechiensis from Guangxi, China, is described as a new species. The species differs from similar L. yangshuoensis by triangular calyx lobe and 3-lobed style, and from L. coriaceifolia by subcoriaceous leaf blade and shorter bracteoles. Its leaf epidermis and pollen morphology were observed by SEM. Diagnostic characters and distribution maps of the above three species are provided too.